2002
DOI: 10.1021/ol0264760
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbenes as Versatile Nucleophilic Catalysts for Transesterification/Acylation Reactions

Abstract: [reaction: see text] Imidazol-2-ylidenes, a family of N-heterocyclic carbenes (NHC), are efficient catalysts in the transesterification between esters and alcohols. Low catalyst loadings of aryl- or alkyl-substituted NHC catalysts mediate the acylation of alcohols with vinyl acetate in convenient reaction times at room temperature. Commercially available and more difficult to cleave methyl esters react with numerous alcohols in the presence of alkyl-substituted NHC to form efficiently the corresponding esters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
114
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 345 publications
(121 citation statements)
references
References 23 publications
2
114
0
3
Order By: Relevance
“…[2][3][4][5][6] NHCs are now used as ligands for transition metals in many important chemical transformations such as Pd-catalyzed coupling reactions, 7) Ru-catalyzed olefin metathesis, 8) Rh-catalyzed hydrosilylations, [9][10][11] and Cu-catalyzed conjugate addition reactions. [12][13][14] Moreover, NHCs have attracted considerable attention as organocatalysts in several reactions such as benzoin condensation, [15][16][17][18][19][20] Stetter reaction, [21][22][23] transesterification/acylation reactions, 24,25) and nucleophilic substitution reactions. [26][27][28] In our study on the use of NHCs as ligands in organic transformations, we have recently reported the addition of diethylzinc to N-sulfonylarylimines catalyzed by Cu-NHC complexes, 29) where NHCs exhibit a strong ligand acceleration effect (LAE).…”
mentioning
confidence: 99%
“…[2][3][4][5][6] NHCs are now used as ligands for transition metals in many important chemical transformations such as Pd-catalyzed coupling reactions, 7) Ru-catalyzed olefin metathesis, 8) Rh-catalyzed hydrosilylations, [9][10][11] and Cu-catalyzed conjugate addition reactions. [12][13][14] Moreover, NHCs have attracted considerable attention as organocatalysts in several reactions such as benzoin condensation, [15][16][17][18][19][20] Stetter reaction, [21][22][23] transesterification/acylation reactions, 24,25) and nucleophilic substitution reactions. [26][27][28] In our study on the use of NHCs as ligands in organic transformations, we have recently reported the addition of diethylzinc to N-sulfonylarylimines catalyzed by Cu-NHC complexes, 29) where NHCs exhibit a strong ligand acceleration effect (LAE).…”
mentioning
confidence: 99%
“…Since the discovery of stable carbenes by Arduengo 3) in 1991, interest in the use of N-heterocyclic carbene-metal complexes have increased, and it has been demonstrated that they are efficient catalysts in important chemical transformations such as Pd-catalyzed coupling reactions, 4) Ru-catalyzed olefin metathesis, 5) and Rh-catalyzed hydrosilylations. [6][7][8] NHCs have also attracted great attention as organocatalysts in several reactions (e.g., benzoin condensation, [9][10][11][12][13][14] Stetter reaction, [15][16][17] transesterification/acylation reactions, 18,19) and nucleophilic substitution reactions). [20][21][22] Recently, our research group as well as other groups have reported the cyanosilylation of aldehydes catalyzed by NHCs.…”
mentioning
confidence: 99%
“…[3][4][5] NHCs have also attracted significant attention as organocatalysts. Several reactions have been catalyzed by NHCs, for e.g., benzoin condensation, [6][7][8][9][10][11] Stetter reaction, [12][13][14] transesterification/acylation reaction, 15,16) and cyanosilylation. [17][18][19] We have previously reported NHC-catalyzed nucleophilic substitution on aromatic heterocyclic rings.…”
mentioning
confidence: 99%